2009
DOI: 10.1583/08-2653.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role for Cryoplasty in the Treatment of Infrainguinal Artery Disease:Case Studies

Abstract: Cryoplasty has been shown to be safe and effective for the treatment of atherosclerotic lesions in the peripheral vasculature and offers the promise of improving on the results of percutaneous transluminal angioplasty (PTA) by limiting dissection, vessel recoil, and restenosis. The PolarCath Peripheral Dilatation System utilizes nitrous oxide rather than the standard mixture of saline and contrast medium to inflate and cool the balloon to the desired temperature of approximately -10 degrees C. Cryoplasty can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…[34][35][36][37][38] Data from several reports featuring these devices do support the TASC II reclassification of femoropopliteal lesions. In a 16-center registry study, Laird et al 39 40 The multicenter Laser Atherectomy for Critical Ischemia (LACI) trial of the CLIRpath Photoablation Atherectomy System involved 423 lesions (41% SFA, 15% popliteal, 41% infrapopliteal; 60% TASC I type D, 28% type C; 11.0-cm median length of treated artery) in 155 limbs (91% with at least 1 occlusion) of 145 CLI patients who were determined to be poor candidates for surgical revascularization.…”
Section: Evidence Supporting the Tasc II Femoropopliteal Reclassificamentioning
confidence: 89%
“…[34][35][36][37][38] Data from several reports featuring these devices do support the TASC II reclassification of femoropopliteal lesions. In a 16-center registry study, Laird et al 39 40 The multicenter Laser Atherectomy for Critical Ischemia (LACI) trial of the CLIRpath Photoablation Atherectomy System involved 423 lesions (41% SFA, 15% popliteal, 41% infrapopliteal; 60% TASC I type D, 28% type C; 11.0-cm median length of treated artery) in 155 limbs (91% with at least 1 occlusion) of 145 CLI patients who were determined to be poor candidates for surgical revascularization.…”
Section: Evidence Supporting the Tasc II Femoropopliteal Reclassificamentioning
confidence: 89%
“…Banerjee et al 6 treated 27 patients with complex peripheral artery stenosis, with a technical success rate of 100% and a 14-month patency rate of 75%. In a multicenter study of cryotherapy to treat 102 cases with femoral-popliteal artery stenosis, Laird et al 24 reported a technical success rate of 85%, with a 9-month patency rate of 70%.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of atherosclerotic lesions can follow different revascularization strategies, including percutaneous transluminal angioplasty (PTA), stent deployment, cryoplasty [25], rotational or directional atherectomy, and interposition of venous, arterial or synthetic grafts. The interventional approach depends on the localization, number and length of vascular lesions, as well as on patient characteristics and concurrent risk factors.…”
Section: Polyamine Synthesis and Functionsmentioning
confidence: 99%